2016
DOI: 10.1080/15321819.2016.1211145
|View full text |Cite
|
Sign up to set email alerts
|

Development of recombinant matrix metalloproteinase-3 based sandwich ELISA for sero-diagnosis of canine mammary carcinomas

Abstract: Matrix metalloproteinase-3 is invariably upregulated in cancerous condition. So we aimed to determine serum level of MMP-3 in canine mammary tumors. The gene was expressed in E. coli system as ~43kDa recombinant protein, which was refolded, purified, and confirmed. Hyperimmune serum was raised against the expressed protein in rabbits and mice to standardize sandwich ELISA. ROC analysis revealed largest area under the curve of 0.998 with sensitivity (100%) and specificity (95%) for a cut-off value of 0.363 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…To date, more than 2000 microsatellite markers have been reported, and many of them have been assigned to linkage groups and specific chromosomes [4]. Some studies have reported a few biomarkers for the diagnosis and prognosis of CMT [19,20]. However, there is a lack of rapid, sensitive and specific biomarkers, which are required for the diagnosis of carcinogenesis in earlier stages.…”
Section: Discussionmentioning
confidence: 99%
“…To date, more than 2000 microsatellite markers have been reported, and many of them have been assigned to linkage groups and specific chromosomes [4]. Some studies have reported a few biomarkers for the diagnosis and prognosis of CMT [19,20]. However, there is a lack of rapid, sensitive and specific biomarkers, which are required for the diagnosis of carcinogenesis in earlier stages.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, need of the hour is to add a few more specific CMT biomarkers to the existing panel for accurate diagnosis and prognosis of the disease. In the last few years, our laboratory has put considerable efforts in search of markers for non-invasive diagnosis and prognosis of CMT (Sunil Kumar et al 2013Pandey et al 2015Pandey et al , 2017Pandey et al , 2018Kaur et al 2016). Advanced research in cancer biology has shown the importance of Hsps as biomarkers of carcinogenesis and their potential in prognosis of some human cancer types (Salda and Romanucci 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, booster doses were given on 7th, 14th, 21st, and 28th days after priming with recombinant proteins mixed with Freund's incomplete adjuvant (Santacruz, USA). Test bleeding was done from tail veins of mice on 29th day to check the titre of the antibodies (Pandey et al 2017). Final bleeding was done by cardiac puncture on 30th day, and sera were harvested and stored at − 20 °C until further use.…”
Section: Production Of Hyperimmune Sera Against Canine Rhsp27 In Micementioning
confidence: 99%
“…Focusing on CMN, according to the consulted literature, over-expression of MMP3 has been described in serum [80] and tissue [69] samples from bitches with mammary carcinoma. The present results confirm that MMP3 plays a role in CMN development since it is over-expressed in both benign and malignant mammary tumours.…”
Section: Discussionmentioning
confidence: 99%